Determination of optimal microwave curing process to obtain the highest early strength of normal concrete - Nawaz, Adnan; Pennung Warnitchai; Thanakorn Pheeraphan; Raktipong Sahamitmongkol; HEC, Pakistan (Pathum Thani, Thailand : Asian Institute of Technology, 2010)
In this research study, an effort has been made to determine an optimum curing process that can give us the highest early compressive strength of normal concrete using microwave energy. The optimal microwave curing process is determined to attain the highest early strength of normal concrete. The optimal microwave cur ing process includes the determination of amount of microwave power output for different levels, time interval between different microwave power levels and the time interval between the microwave curing and the compressive strength test. A series of experi ments are carried out using trial and error method to achieve the optimal curing process. The consequential process can turn out 50 - 60% of 7 days compressive strength of normally cured concrete within 10.5 hours after mixing. After obtaining the optimal cu ring process for normal concrete, same procedure is applied on concrete mixes of different compositions, containing fly ash in different amounts, for comparison. The outcome illustrates that the optimum curing process worked out is not only valid for the n ormal concrete but also for the concrete containing fly ash as a replacement of cement content.
Submitted in partial fulfillment of the requirements for the Degree of Master of Engineering in Structural Engineering, School of Engineering and Technology
Research report (M. BA.) - Asian Institute of Technology, 2010
Keywords: Concrete -- Curing; Microwage heating